Дефіцит вітаміну D і його роль у розвитку порушень обміну речовин за цукрового діабету - Комісаренко, Ю. І. (Clinical Endocrinology and Endocrine Surgery, 2013)
Reviewed were the data pertinent of the effects of vitamin D3 upon carbohydrate, lipid and protein metabolism, structure and function of pancreatic β-cells at diabetes mellitus. Some mechanisms of disturbance of vitamin D3 metabolism at the above pathology and perspectives for its clinical application were described.